Positive Propoxyphene Test Result for Drug-Free Serum or Plasma Obtained When Using the Roche Cobas c502 Urine Propoxyphene Screening Test. (11th September 2019) - Jagannathan, Geetha; Curtis, Mark; Stickle, Douglas
Abstract: Introduction: During a recent autopsy case, we were asked to investigate possible surreptitious inpatient use of drugs of abuse (DOA). As serum was the only sample type available for this subject, we initially ran serum samples on our urine drugs of abuse (DOAU) assays. Results were unexpectedly positive for propoxyphene (PPX). We immediately determined, however, that all plasma or serum samples, selected randomly from the hospital laboratory as presumed-negative controls, produced PPX-positive test results on the urine PPX assay. We report our investigation of this finding. Methods: The PPX urine assay (Roche Cobas c502, Indianapolis, IN) is a semiquantitative screening test based on kinetic interaction of microparticles in solution (KIMS), with a cutoff concentration of 300 ng/mL. The assay was conducted according to manufacturer's instructions, other than the substitution of plasma for urine as described below. Plasma or urine samples were obtained from to-be-discarded samples residual from routine testing in the hospital laboratory. Results: Pooled plasma required a 1:4 dilution with drug-free urine to produce a PPX-negative test result. Bovine serum albumin (7 g/dL), mimicking total protein of plasma, produced a PPX-negative test result. Pretreatment of plasma using heterophilic antibody blocking reagent (Scantibodies Laboratory, Santee, CA) did not alter the PPX-positive test result. However, pretreatment of plasma by polyethylene glycol (PEG) to precipitate immunoglobulins altered the test result to PPX negative. PEG pretreatment did not alter PPX-positive results for PPX-spiked urine. Conclusions: An autopsy case produced an incidental finding of false-positive test results for plasma tested on the Roche urine PPX assay. Based on PEG pretreatment data, it appears that some common component of immunoglobulins in plasma produces a positive interference in this assay. In principle, rare circumstances of severe renal dysfunction to produce plasma-like urine could potentially lead to false-positive results with the Roche urine PPX screening test.